Renter Power for Better Living: Introduction: FCS5230-02/FY781, rev. 12/2005 - Harrison, Mary N. (EDIS, 2019)
Information in this book will help you protect the health of your family and your financial well-being. It will teach you to care for your home and make it a better place to live. This document is FCS5230-02, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date June 2002. Revised December 2005.